2014
DOI: 10.1371/journal.pone.0109723
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vesicular Glutamate Transporters VGLUT1 and VGLUT2 in the Rat Dental Pulp and Trigeminal Ganglion following Inflammation

Abstract: BackgroundThere is increasing evidence that peripheral glutamate signaling mechanism is involved in the nociceptive transmission during pathological conditions. However, little is known about the glutamate signaling mechanism and related specific type of vesicular glutamate transporter (VGLUT) in the dental pulp following inflammation. To address this issue, we investigated expression and protein levels of VGLUT1 and VGLUT2 in the dental pulp and trigeminal ganglion (TG) following complete Freund’s adjuvant (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
(57 reference statements)
2
15
1
Order By: Relevance
“…The proportion of VGLUT2+ neurons in the mouse TG in the present study (37%) was lower than previously reported: from only a few neurons or almost all neurons in rat DRG (Oliveira et al, 2003; Landry et al, 2004), 65–69% in mouse DRG (Brumovsky et al, 2007; Malet et al, 2013), 15% or 85% in rat TG (Li et al, 2003; Yang et al, 2014). This variability may be due to differences in sensitivity of the antibodies used, choice of threshold levels for VGLUT2-immunoreactivity, species, or DRG vs. TG.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The proportion of VGLUT2+ neurons in the mouse TG in the present study (37%) was lower than previously reported: from only a few neurons or almost all neurons in rat DRG (Oliveira et al, 2003; Landry et al, 2004), 65–69% in mouse DRG (Brumovsky et al, 2007; Malet et al, 2013), 15% or 85% in rat TG (Li et al, 2003; Yang et al, 2014). This variability may be due to differences in sensitivity of the antibodies used, choice of threshold levels for VGLUT2-immunoreactivity, species, or DRG vs. TG.…”
Section: Discussioncontrasting
confidence: 92%
“…Recent reports, including studies using VGLUT2-deficient mice, suggest that VGLUT2-dependant glutamate release from primary sensory afferents plays an important role in normal acute nociception and pathologic pain (Moechars et al, 2006; Leo et al, 2009; Liu et al, 2010; Scherrer et al, 2010; Lagerstrom et al, 2011; Rogoz et al, 2012). Specifically, VGLUT2 increases in the trigeminal ganglion (TG) neurons following Complete Freund’s Adjuvant (CFA)-induced pulpal inflammation, suggesting that VGLUT2-dependant glutamate signaling may mediate pulpal inflammatory pain (Yang et al, 2014). However, little is known about the alteration in expression of TRPM8 and the associated VGLUTs in TG neurons following dental pulp inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate is the major excitatory neurotransmitter in the vertebrate central nervous system (Fremeau et al, 2004, Wojcik et al, 2004) and is used by primary sensory neurons in TG (Yang et al, 2014) and DRG (Brumovsky et al, 2007, Miller et al, 2011) of the peripheral nervous system. In primary sensory neurons in DRG, neurotransmitter glutamate production utilizing the glutamate-glutamine cycle is important for sensory function (Miller et al, 1993, Miller et al, 2002, Miller et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, VGLUT1 and VGLUT2 have been more intensively studied due to the availability of reliable specific antibodies. Both VGLUT1 & 2 are present in somatic and visceral DRG sensory neurons (Hwang et al, 2004, Brumovsky et al, 2007, Miller et al, 2011, Yang et al, 2014), in enteric neurons (Brumovsky et al, 2011), and in vagal afferent neurons innervating the gastrointestinal tract and heart (Lawrence and Jarrott, 1994, Lawrence, 1995, Berthoud et al, 1997, Corbett et al, 2005, Raab and Neuhuber, 2007). In the current study, the discovery of many neurons expressing GLS, VGLUT1, and VGLUT2 provides novel information regarding the presence of glutamatergic neurons in rat cardiac intrinsic ganglia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation